Long-term effects of a food pattern on cardiovascular risk factors and age-related changes of muscular and cognitive function. Issue 39 (25th September 2020) - Wernicke, Charlotte; Apostolopoulou, Konstantina; Hornemann, Silke; Efthymiou, Andriana; Machann, Jürgen; Schmidt, Sein; Primessnig, Uwe; Bergmann, Manuela M.; Grune, Tilman; Gerbracht, Christiana; Herber, Katharina; Pohrt, Anne; et al.
Abstract: Introduction: The mean age of the German population increased over the last years, which resulted in a higher prevalence of cardiovascular diseases, type 2 diabetes, cognitive impairment, sarcopenia and bone fractures. Current evidence indicates a preservation of human wellbeing in the elderly by a healthy diet, although the recommended macronutrient composition and quality remains unclear and needs further long-term investigation. In this context we investigate the effect of a specific dietary pattern on age-related disorders in a randomized controlled multi-center trial (RCT). Methods: We assess the effect of a specific dietary pattern (NutriAct) with a high proportion of unsaturated fat, plant proteins and fibres (fat 35%–40% of total energy (%E) of which 15%E–20%E monounsaturated fatty acids (MUFA) and 10%E–15%E polyunsaturated fatty acids (PUFA), 15%E–25%E proteins, ≥30 g fibres per day and 35%E–45%E carbohydrates) on age-related impairment of health within a 36-months RCT conducted in the region of Berlin and Potsdam. 502 eligible men (n = 183) and women (n = 319), aged 50 to 80 years, with an increased risk to develop age-related diseases were randomly assigned to either an intervention group focusing on NutriAct dietary pattern or a control group focusing on usual care and dietary recommendations in accordance to the German Nutrition Society (DGE). In the intervention group, 21 nutrition counsellings as well as supplementation of rapeseed oil, oil cake and specific designed foods are used to achieve the intended NutriAct dietary pattern. The primary outcome is a composite endpoint of age-related disorders, including cardiovascular morbidity, decline of cognitive function as well as clinical features of sarcopenia. Secondary outcomes include diet-induced effects on quality of life, depression, frailty, cardiovascular function, bone density, fat distribution pattern, glucose, lipid and energy metabolism, as well as the identification of biomarkers linked with age-related disorders. Discussion: The findings of this trial will provide clinically relevant information regarding dietary effects on age-related impairment of health and will contribute to the definition of the optimal macronutrient composition in the context of healthy aging in the German population. Abstract : Supplemental Digital Content is available in the text